Application of Pediococcus acidilactici BD16 (alaD+) expressing L-alanine dehydrogenase enzyme as a starter culture candidate for secondary wine fermentation. Issue 1 (1st January 2021) - Sharma, Anshula; Noda, Masafumi; Sugiyama, Masanori; Kumar, Balvir; Kaur, Baljinder
Abstract: Secondary fermentation is generally recommended to improve the aroma, flavour, overall acceptability and stability of the wines. Pediococcus acidilactici BD16 expressing L-alanine dehydrogenase gene is hereby proposed as a starter culture bacterium for the value addition of ginger, kiwi, plum and rose wines through secondary fermentation. Secondary fermentation using Pediococcus acidilactici BD16 ( alaD + ) imparted a natural sweetness and several health-promoting attributes to the dry wines, thereby improving their sensory and quality attributes. GC-MS-based metabolic fingerprinting further revealed the presence of significantly higher levels of L-alanine and many bioactive secondary metabolites and flavour enhancers such as 3-butynol, acetaldehyde, alaninol, aminopentols, benzene methanol, octanoic acid, ribitol, etc. and therapeutic ingredients such as 8-azanonane, actinobolin, adamantanemethylamine, aminononadecane, amphetamine, benzeneethanamine, guanosine, heptadecanenitrile, isopropyluriedoacetate, octanoic acid, nortriptyline and rimantadine in the secondary fermented wines. Further, a probable metabolic pathway was constructed to indicate major metabolic biotransformations in the wines which accounted for the improved quality attributes and strongly anticipated their therapeutic potential. This study is probably the first of its kind to highlight the application of P. acidilactici BD16 ( alaD + ) for in situ L-alanine production during secondary wine fermentation for enhancing organoleptic and therapeutic attributes of interest to health-conscious consumers.